Natural Killer-Like B Cells Secreting Interleukin-18 Induces a Proinflammatory Response in Periodontitis - Zhang, Ye; Kuang, Wei; Li, Danfeng; Li, Yu; Feng, Yi; Lyu, Xinwei; Huang, Gao-Bo; Lian, Jian-Qi; Yang, Xiao-Fei; Hu, Cheng; Xie, Yajuan; Xue, Song; et al. (Frontiers in Immunology, 2021)
Natural killer-like B (NKB) cells, which are newly identified immune subsets, reveal a critical immunoregulatory property in eradication of microbial infection via secretion of interleukin (IL)-18. For the first time, this study investigated the role of NKB cells and secreting IL-18 in the pathogenesis of periodontitis. In this study, NKB cells percentage and IL-18 concentration in peripheral blood and periodontium in periodontitis patients was measured using flow cytometry and ELISA. The role of IL-18 in regulating periodontal inflammation was examined in Porphyromonas gingivalis (P. gingivalis)-induced periodontitis murine model. Peripheral and periodontal-infiltrating CD3-CD19+NKp46+ NKB cells, which were the main source of IL-18, were elevated and correlated with attachment loss in periodontitis patients. In vitro IL-18 stimulation promoted proinflammatory cytokine production by periodontal ligament cells. P. gingivalis infection induced elevation of IL-18 receptor in periodontium in periodontitis murine model. IL-18 neutralization not only suppressed P. gingivalis-induced alveolar bone resportion, but also inhibited recruitment of antigen-nonspecific inflammatory cells into the periodontium probably via dampening expressions of cytokines, chemokines, and matrix metalloproteinases. NKB cells-secreting IL-18 appeared to be an important mediator in inflammatory response following intraoral P. gingivalis infection. These findings might be relevant to development of immunotherapies for periodontitis.